Nursing of a patient with periarthritis of the shoulder treated by Traditional Chinese Medicine ointment rubbing combined with Traditional Chinese Medicine hot pack therapy (中药膏摩联合中药热奄包治疗“五十肩”1例的护理体会) - XU Yaqi (徐雅琪); WANG Chunhong (王春红); ZHAO Xin (赵欣); XU Weihong (徐卫红); GAO Chen (盖晨); YAO Wei (姚微); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the nursing management for a patient with periarthritis of the shoulder treated by Traditional Chinese Medicine (TCM) ointment rubbing combined with Traditional Chinese Medicine hot pack therapy. Based on the TCM theory, meridians and collaterals points were selected by syndrome differentiation, and composition of Chinese herbal medicine was determined. The TCM ointment rubbing combined with TCM hot pack therapy was carried out, in coordination with life support, functional exercise and extended care, to improve the function of shoulder joint and recovery of the patient. (本文总结了1例中药膏摩联合中药热奄包治疗“五十肩”患者的护理经验, 通过辨证选取经络穴位, 确定中药组成, 选用合适的介质, 基于中医基础理论, 开展中药膏摩和中药热奄包治疗, 同时做好生活指导、功能锻炼、延续护理等措施, 减轻患者疼痛, 改善患者肩关节功能, 促进患者早日康复。)